Idealtipe Birokrasi Weberian Dalam Sistem Pendidikan: Implikasi Terhadap Efisiensi dan Efektivitas Manajemen - Riko Anas; Silfia Hanani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This concept of the Weberian bureaucratic ideal-type has been the basis for many organisations and governments around the world. While it is not always possible to achieve all of these characteristics in practice, these ideals provide a view of how an efficient and effective organisation should operate. The purpose of this research is to explain the Weberian Bureaucratic Ideals in the Education System: Implications for Management Efficiency and Effectiveness. The method used in this study uses qualitative research procedures using a research approach in the form of a literature study. Sources of information in this study were reviewed from various novel sources of literature, research reports, scientific essays, theses, dissertations and posts both print and electronic related to the Idealtype of Weberian Bureaucracy in the Education System: Implications for Management Efficiency and Effectiveness. The results of this study show that the application of the ideal-type concept of Weberian bureaucracy in the education system has significant implications for management efficiency and effectiveness. The principles of Weberian bureaucracy, such as rationality, clear rules, strict hierarchy, specialisation, impersonality and separation of ownership and management, create the basis for more rational decision-making, efficient administration and better achievement of educational goals. In the context of decision-making, the principles of rationality and clear rules ensure that policies and decisions are based on objective criteria and relevant data.